APPLYING CONVERSATION STRATEGY TO IMPROVE STUDENTS' COMPREHENSION IN SPEAKING AT SMP KARTIKA XX-2 MAKASSAR (Karya Ilmiah Mahasiswa (KIMA), 2023)
This research aimed to apply a conversation strategy to improve students’ comprehension in English. The research was conducted by using a pre-experimental design, which was carried out through four steps, they were pre-test, treatment, post-test, and questionnaire. The objective of the research was to know the results of the teacher's way of giving an understanding of the learning by using a conversation strategy and to see if a conversation strategy could give rise to a student's comprehension of speaking ability in learning English. The technique of analyzing the data of this research was applied quantitative approach and pre-experimental design. The data were taken from pre-test, post-test, and questionnaire. The result of the data analysis showed that the post-test average value was greater than the pre-test average value post-test, which was 67.56 > 50.89. It was supported by the result of the data paired sample t-test shows that the value of sig 2 (tailed) is 0.00, meaning it was less than 0.05. Thus, the data showed that the alternative hypothesis (Ha) is accepted. In addition, the students responded through a questionnaire using 4 positive statements and 2 negative statements, the researcher concluded that the students were given positive responses. The Researcher Concludes that teaching speaking by using a conversation strategy could increase the student's comprehension of speaking.